ASSESSMENT OF ORGANIC ACID CONTENT, AND BRIX VALUE OF REPRESENTATIVE INDIGENOUS FERMENTED PLANT BEVERAGES OF THAILAND - Chaiyasut, Chaiyavat; Makhamrueang, Netnapa; Peerajan, Sartjin; Sivamaruthi, Bhagavathi Sundaram (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Objective: In Thailand, people believe that the fermented plant beverages (FPBs) have the pharmaceutical effects and consumption of FPBs cure the diseases. This study was conducted to detect and quantify the organic acids, pH, and Brix value of the commonly using FPBs of Thailand. Methods: The samples were collected from all the region of Thailand. The total acidity, pH, and organic acid content were measured by titration, pH meter, and high-performance liquid chromatography methods, respectively. The sugar content of the sample was assessed by Brix value determination using a refractometer. Results: All the tested FPBs showed the pH value of 2-4 except sample no. 64 (pH 6.49) and 65 (pH 5.72). The acidity of the samples showed a range of ~0.1-2.5% of lactic acid equivalent. The acidity of sample no. 64 and 65 was not in detectable level. As per the Thai Community Product Standard (TCPS) - No. 481/2004, all the samples were qualified for the human consumption except sample no. 64 and 65. About 34, 17, 58, 53, 8, 6, 12, and 1 samples were detected with 0.018-0.241, 0.015-0.389, 0.028-1.244, 0.052-0.550, 0.024-0.267, 0.049-0.373, 0.025-0.980, and 0.31 mg/mL of as tartaric, malic, lactic, acetic, citric, sorbic, fumaric, and propionic acids, respectively. The sugar content of the sample no. 9 and 49 was >55 % of Brix value, while other tested samples were <50%. Conclusion: All the tested FPBs were harmless to human regarding organic acid content, pH, and Brix value except sample no. 64 and 65 as per the TCPS. Further studies are mandatory to explore the microbial and pharmaceutical nature of traditional FPBs and other fermented foods of Thailand. Keywords: Brix value, Fermented plant beverages, Morinda, Organic acids, pH.